La législation en faveur de l’enseignement des Langues et Cultures Nationales au Cameroun : mesure d’audience dans l’Adamaoua et implications glottopolitiques - Gilbert Daouaga Samari (Recherches en Éducation)
The ban of National Languages and Cultures from schools during the colonial period has been maintained even after 1960, the year of Independence of Cameroon. It means that the Language Policy implemented, which consisted to use French and English as Languages of Instruction had not changed. The result is that students could not use the Languages they mastered; they should learn through those they did not use. It is in 1996 that Cameroon began to take measures in favor of National Languages; until today, there are official texts which support the use of these Languages in Education. However, a survey we carried out in the Adamawa Region shows that most educational Actors do not know these texts. Our view is that this could slow down the Implementation of this new policy.